Circulating PACAP peptide and PAC1R genotype as possible transdiagnostic biomarkers for anxiety disorders in women: a preliminary study - Ross, Rachel A. (Neuropsychopharmacology, 2020)
Pituitary adenylate cyclase activating polypeptide (PACAP, gene Adcyap1) is a neuropeptide and hormone thought to play a critical role in stress response (Stroth et al., Ann NY Acad Sci 1220:49−59, 2011; Hashimoto et al., Curr Pharm Des 17:985-989, 2011). Research in humans implicates PACAP as a useful biomarker for the severity of psychiatric symptoms in response to psychological stressors, and work in rodent models suggests that PACAP manipulation exerts downstream effects on peripheral hormones and behaviors linked to the stress response, providing a potential therapeutic target. Prior work has also suggested a potential sex difference in PACAP effects due to differential estrogen regulation of this pathway. Therefore, we examined serum PACAP and associated PAC1R genotype in a cohort of males and females with a primary diagnosis of generalized anxiety disorder (GAD) and nonpsychiatric controls. We found that, while circulating hormone levels were not associated with a GAD diagnosis overall (p = 0.19, g = 0.25), PACAP may be associated with GAD in females (p = 0.04, g = 0.33). Additionally, among patients with GAD, the risk genotype identified in the PTSD literature (rs2267735, CC genotype) was associated with higher somatic anxiety symptom severity in females but lower somatic anxiety symptom severity in males (−3.27, 95%CI [−5.76, −0.77], adjusted p = 0.03). Taken together, the associations between the risk genotype, circulating PACAP, and somatic anxiety severity were stronger among females than males. These results indicate a potential underlying biological etiology for sex differences in stress-related anxiety disorders that warrants further study.